ANALISIS KECENDERUNGAN PENELITIAN KEBIJAKAN PEMULIHAN EKONOMI PASCA PANDEMI DI INDONESIA - Nur Saribulan (Fakultas Politik Pemerintahan IPDN, 2023)
Abstract Economic recovery has attracted all government around globe recently, without exception for Indonesian authorities. Due to large number of studies associated with economic recovery research, this study aims to mapping those trends using bibliometric analysis using Microsoft Excel and Vosviewer as an instrument analysis and data visualization. The results show that the development of the trend publication on the theme economic recovery in Indonesia increased with the highest number by 19 articles on 2022. As for citation, the highest citation is found stood at 47 in journal Bulletin of Indonesian Economic with article title “Indonesia Under the New Normal: Challenges and the Way Ahead” with the result that economic recovery in Indonesia still focus on dealing with short-term effects on pandemic in which government focused more on supporting poor and near-poor groups, and preparing for health and educational sector. Based on publication map of co-authorship is classified into 35 cluster with Indonesia as the affiliation country of author with the highest number of publications, while based on publication map of co-occurrence formed 15 clusters. Keywords: economic recovery; economic resilience, policy, bibliometric analysis